Principles of engineering - Handley, Brett; Coon, Craig; Marshall, David M. (PLTW project lead the way, 2012)
PRINCIPLES OF ENGINEERING will help readers better understand the engineering concepts, mathematics, and scientific principles that form the foundation of the Project Lead the Way (PLTW) Principles Of Engineering course. Important concepts and processes are explained throughout using full-color photographs and illustrations. Appropriate for high school students, the mathematics covered includes algebra and trigonometry. Strong pedagogical features to aid comprehension include: Case Studies, boxed articles such as Fun Facts and Points of Interest, Your Turn activities, suggestions for Off-Road Exploration, connections to STEM concepts, Career Profiles, Design Briefs, and example pages from Engineers' Notebooks. Each chapter concludes with questions designed to test the reader's knowledge of information presented in the chapter, along with a hands-on challenge or exercise that compliments the content and lends itself to exploration. Key vocabulary terms are highlighted throughout the book and emphasized in margin definitions